Photovoltaic spectral conversion materials: the role of sol–gel processing - Correia, Sandra F. H. (2023)
Photovoltaic (PV) technologies are in constant development, but all of them present limitations. One way of increasing the spectral range of absorbed sunlight, is through the use of spectral converters able to absorb radiation which is not used by PV cells and convert it to radiation with a usable energy. They can be converting layers (down-shifting or up-converting) applied on PV cells surface or luminescent solar concentrators, complementary devices specially indicated for urban integration of PV devices. Most of the works focus on the optically active centers, but the choice of the host matrix to disperse them is also of great importance. In this sense, the use of sol-gel processed materials have been applied due to the appealing synthesis procedure inherent of this technique. Here, a review on state-of-the-art spectral converting devices is provided, with special attention to the studies in which sol-gel processed materials play a determinant role.